Draft Sikkim Tenth Five Year Plan 2002-07 and Annual Plan 2002-03 Volume-I - Planning Commission (Planning Commission, 2002)
Sikkim is a strategic, tiny hill State with an area of 7096 Sq.Km. The lofty mountains, perennial glaciers, lush green hills, valleys and the rich biodiversity constitute the magnificent watershed both for sustainable social & economical development and also for enriching the traditional and cultural heritage of the people of Sikkim. The State joined the democratic main stream of the Indian Union only 26 years ago in 1975. The Democratic processes have generated ample social and economic security to the mass. Their choices are broadened and their hopes transformed into opportunities. The journey so far has been rewarding and the process of development satisfactory.
Planning and Development Department Government of Sikkim